2010
DOI: 10.1089/ten.tea.2009.0640
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Pancreatic Islets Within Nano-Thin Functional Polyethylene Glycol Coatings for Enhanced Insulin Secretion

Abstract: Covalent attachment of polymers to cells and tissues could be used to solve a variety of problems associated with cellular therapies. Insulin-dependent diabetes mellitus is a disease resulting from the autoimmune destruction of the b cells of the islets of Langerhans in the pancreas. Transplantation of islets into diabetic patients is an attractive form of treatment, provided that the islets could be protected from the host's immune system to prevent graft rejection, and smaller numbers of islets transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 67 publications
(64 reference statements)
2
83
0
1
Order By: Relevance
“…Recently, it was shown that, GLP-1 coated islets exhibited a higher response to glucose challenge, in terms of insulin secretion, compared to the untreated islets in vitro. (Kizilel, Scavone, Liu, Nothias, Ostrega, Witkowski and Millis 2010) This suggested that similar effect could be observed when GLP-1 is immobilized within the PEG hydrogel capsule around the islet. Therefore, it was important to design PEG hydrogel coatings with high GLP-1 concentrations at points closer to the surface in the case of islet microencapsulation within PEG hydrogel.…”
Section: 0e-04mentioning
confidence: 73%
“…Recently, it was shown that, GLP-1 coated islets exhibited a higher response to glucose challenge, in terms of insulin secretion, compared to the untreated islets in vitro. (Kizilel, Scavone, Liu, Nothias, Ostrega, Witkowski and Millis 2010) This suggested that similar effect could be observed when GLP-1 is immobilized within the PEG hydrogel capsule around the islet. Therefore, it was important to design PEG hydrogel coatings with high GLP-1 concentrations at points closer to the surface in the case of islet microencapsulation within PEG hydrogel.…”
Section: 0e-04mentioning
confidence: 73%
“…The LbL coating of islets based on streptavidin/biotin anchoring as a driving force for the LBL was also developed (Dai et al, 2007;Kizilel et al, 2010). PEGylated multilayers were grown using LbL assembly of biotinylated PLL and streptavidin.…”
Section: The Lbl Assembly Based On Covalent And/or Specific Interactionsmentioning
confidence: 99%
“…In another example, the rat islet cell membranes were first biotinylated through covalent reaction of the membrane proteins and NHS-ester groups of NHS-PEG-biotin. The second layer of streptavidin was followed by a layer of a biotin-PEG conjugate with the insulinotropic Glucagon-like Ppetide 1 (GLP-1) (Kizilel et al, 2010). GLP-1 is a 30-amino acid peptide hormone produced in the intestinal epithelial endocrine L-cells.…”
Section: The Lbl Assembly Based On Covalent And/or Specific Interactionsmentioning
confidence: 99%
“…Several methods of conformal coating have been developed recently, including covalent surface attachment of polyethylene glycol (PEG), known as 'PEGylation' [18], and layer-by-layer encapsulation [19][20][21][22][23][24][25][26][27][28]. Nano-layers with different combinations of components, including streptavidin and biotin-PEG derivatives [19,24], complement receptor 1 and heparin [25], and PEG-lipid and poly(vinyl alcohol) [26,27], have been previously researched as islet surface coatings.…”
Section: Introductionmentioning
confidence: 99%